Legal Protection for Consumers in E-Commerce Transactions Through Facebook Marketplace with Split Payment System - Ningsih, Sri Eva; Arpangi, Arpangi (UNISSULA Semarang, 2025)
Abstract. In today's era, technology is something that is very much needed by every group, the use of technology brings positive forms to facilitate communication and so on, but the use of technology is often misused such as electronic-based fraud or what we often know as e-commerce. Electronic commerce (e-commerce) has now reformed conventional trade, where the interaction between consumers and business actors that was previously carried out directly, which with the existence of electronic commerce, has now become an indirect interaction. The definition of e-commerce is also stated in Article 1 paragraph (2) of the ITE Law (Information and Electronic Transactions) No. 11 of 2008 which regulates,